OR23-06 Is the Improved Glucose Homeostasis in Patients with Acromegaly Treated with Pegvisomant Caused by Improved Glucagon Secretion? - Jørgensen, miss, Nanna Thurmann (J Endocr Soc, 2020)
Context: Active acromegaly is associated with impaired glucose metabolism, which improves upon treatment. Treatment with first generation somatostatin analogues (SSA) has a detrimental effect on insulin secretion, but the effect on glucose homeostasis is neutralized by the reduction in growth hormone (GH) and Insulin-like growth factor-1 (IGF-1). Treatment with GH receptor antagonists has a more favorable effect on glucose homeostasis. Objective: To describe the secretion of glucose, insulin, glucagon, glucagon-like peptide-1 (GLP1), and glucose-dependent insulinotropic polypeptide (GIP) in surgically treated patients with acromegaly treated or not with somatostatin analogues, either as monotherapy (SSA) or in co-treatment with pegvisomant (SSA+PEG), respectively, compared to healthy controls. Methods: Descriptive study of data from 23 surgically treated, non-diabetic patients with acromegaly and 6 healthy controls. After an overnight fast, all participants underwent a three-hour 75 g oral glucose tolerance test (OGTT) and subsequently a three-hour isoglycaemic intravenous glucose infusion on a separate day. Analysis: Baseline hormone concentrations, time to peak and area under the curve (AUC) on the OGTT-day, and the incretin effect in the patient groups and controls were compared using analysis of variance with post-hoc analysis. Results: The total group of patients treated with somatostatin analogues (N=15) had numerically impaired glucose, insulin, GLP1 and glucagon responses (AUC, P>0.05 respectively), and an impaired GIP-response (AUC, P=0.007) during OGTT as compared to patients not treated with somatostatin analogues and healthy controls. Similarly, the incretin effect was numerically impaired. Patients co-treated with pegvisomant (SSA+PEG, N=4) had a numerically increased secretion of insulin and glucagon compared to patients on SSA (N=11) during OGTT (insulin AUC mean (SEM), SSA+PEG 49 nmol/l*min (8.3) vs SSA 25 (3.4), P>0.05) [healthy controls 62 (13.6)]; glucagon AUC, SSA+PEG 823 pmol/l*min (194) vs SSA 332 (69), P>0.05) [healthy controls 946 (233)]). GIP secretion remained significantly impaired, whereas GLP1 secretion was numerically increased with PEG (SSA+PEG 3088 pmol/l*min (366) vs SSA 2401 (239), P>0.05) [healthy controls 3972 (451)] but remained without a glucose-dependant increase as in SSA. The incretin effect numerically increased in SSA+PEG compared to SSA (SSA+PEG 49.9% (13.9) vs SSA 33.6% (47.4), P>0.05) [healthy controls 55.5% (7.7)]. Conclusion: Somatostatin analogues impaired the secretion of both insulin, glucagon and incretin hormones secretion. Co-treatment with pegvisomant seemed to counteract the somatostatinergic inhibition of the glucagon secretion and improved the insulin response to OGTT. We speculate that pegvisomant exerts its action via GH-receptors on pancreatic δ-cells.